STUDI SANITASI PENGELOLAAN LINGKUNGAN OLEH MASYARAKAT PINGGIR KALI DI KELURAHAN KOTO PANJANG IKUR KOTO KECAMATAN KOTO TANGAH KOTA PADANG - Tessa Melinda; Helfia Edial; Endah Purwaningsih (JURNAL BUANA, 2020)
Abstract This study aims to obtain data and information about the provision of clean water facilities, landfills, sewerage and human waste/toilet in Koto Panjang Ikur Koto. This type of research is quantitative descriptive. The research population was 506 households. The research sample of 83 households. The type of data needed is primary data and secondary data. Data collection techniques are observation, questionnaire, interview and documentation. The collected data is analyzed using the percentage formula. The results of this study indicate: 1) Provision of clean water facilities using well water, 2) Provision of waste disposal facilities using waste baskets with traditional management systems (burned, discharged into pits, into rivers), 3) Provision of sewerage facilities generally uses pipe paralon and its management by means of dilution (discharged into rivers, gutters or the sea), 4) Provision of facilities for the disposal of human waste / toilets generally the community has a family toilet, while others do MCK activities in rivers and public toilets.